Acupuncture for symptoms management in Korean breast cancer survivors: a prospective pilot study. Issue 3 (June 2019) - Kim, Tae-Hun; Kang, Jung Won
Background: There is an unmet need for effective treatment of the various treatment-related symptoms experienced by breast cancer survivors. These symptoms could be alleviated by acupuncture. Although several lines of evidence in Western countries suggest that acupuncture has a beneficial effect on symptoms in breast cancer survivors, few relevant studies have been conducted in Korean patients. This pilot study assessed the feasibility of acupuncture for a variety of treatment-related symptoms in Korean breast cancer survivors. Method: From October 2015 to March 2016, we recruited patients who had undergone treatment for breast cancer and subsequently reported symptoms, including aromatase inhibitor-related knee pain, vasomotor symptoms, insomnia, sexual dysfunction and post-mastectomy pain in the chest wall or shoulder. The women received 4 weeks of symptom-specific acupuncture followed by a further 4 weeks of follow-up to evaluate the feasibility of acupuncture for this indication, and its impact on common and symptom-specific outcome variables. Results: Eight study participants were recruited over a period of 6 months, six of whom completed the planned acupuncture treatment and follow-up assessments. A total of 78 acupuncture sessions were performed. We found that acupuncture was feasible, with only six minor self-limiting acupuncture-related adverse events. Most of the women felt that they had benefitted from participation in the study. The preliminary analysis indicated improvement in common symptom-specific outcomes. Conclusion: Our findings suggest that acupuncture is feasible, but low recruitment rates should be considered when considering future acupuncture research in Korean breast cancer survivors. Rigorous evaluation of this symptomatic treatment strategy is now needed in the Korean population.